Thermodynamic modelling and simulation of a Pumped Hydro - Compressed Air Energy Storage System (PH-CAES) - Daniel Leon Ferreira Pottie (2019)
The fundamental role of electricity in modern society cannot be overstated. In a ever increasing energy consumption world, shifting from fossil fuels towards a more renewable generation system will incur in deep changes, not only in the electric system, but also on society itself. In this rapidly changing scenario, Energy Storage Systems (ESS) are seen as a powerful ally to assist the transition. In this research, a novel ESS named Pumped Hydraulic Compressed Air Energy Storage proposes replacing the air the compressor and turbine, utilized in conventional CAES system by hydraulic pumps and turbines. Directly compressing the air, as is done in CAES is a energy demanding process, in which the gas is confined to a small chamber and undergoes a rapid transformation. As a result, its temperature increases considerably, which in turn, require special materials and methods to be handled. Instead of, a hydraulic pump pushed water into a closed tank, slowly and indirectly compressing the air inside. This way, a great deal of simplicity is achieved, temperature increase and power requirement are diminished and the system operates as a hybrid between PHES (charging and discharging) and CAES (storage medium). An extensive literature review is performed, aiming to describe and explain the possible types and applications ESS on the energy generation and distribution market. Following, the new system operating sequence is completely described and modelled under the scope of the Laws of Thermodynamics, fluid mechanics and heat transfer concepts. The proposed methodology is then applied to a laboratory scale simulation, performed in Matlab. Several operating scenarios were simulated, in order to assess the system performance over a wide range of conditions. The results found proved that the new system is able to quickly respond, generating a stable power output. Also, replacing the compressor by hydraulic pumps, and indirectly compressing the air with water results in a considerable decrease in power consumption. This way, a round trip efficiency figure of 45% is achieved, and considering the proposed system size and simplicity, it is considered a promising. To test this, the system efficiency is compared to several CAES literature references, and its value is comparable to larger, more complex and potentially expensive systems, which usually depend on multiple heat exchangers, burning fuel or an external.